Theory and methods in political science - Marsh, David , 1946-; Stoker, Gerry (Kirby Street, London : Palgrave Macmillan, 2010)
Now with substantial extra coverage of methodological issues and an additional chapter on the philosophy of politics, this widely-used text introduces students to the approaches and methods of political science
1. Theory and approaches -- 2. Methods and research design
Includes bibliographical references (p. 343-383) and index
Keywords: Political science; Political science -- Methodology